The Efficacy of Injection of 0.25 mg/kg Dexamethasone after Induction of Anesthesia on Reducing Tonsillectomy Morbidities. - Saad M. Al Muhayawi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Tonsillectomy is one of the most commonly performed surgical procedures in otolaryngology practice. Nausea, vomiting, pain, decreased oral intake and dehydration are frequently associated with tonsillectomy. This study demonstrates the effect of prophylactic administration of dexamethasone as a single dose on post tonsillectomy morbidities. This was a comparative cross-sectional study of pediatric patients (3-15 years) attending the otolaryngology outpatient clinics at King Abdulaziz University Hospital between October 2010 and December 2012. A sample of 100 patients, divided into two groups of 50 patients was included for analysis. The first group received intravenous dexamethasone (0.25 mg/kg) as a single dose with induction of anesthesia. In the second, control, group, no pre-operative dexamethasone was administered. The outcome was assessed by a questionnaire distributed to both groups to evaluate post-operative nausea, vomiting, pain and early oral feeding. Pain score was assessed using a visual analogue scale (ranging from 0 to 10. Our results showed a statistically significant reduction in morbidity associated with tonsillectomy, supporting the administration of single dose intravenous dexamethasone during tonsillectomy.